2018
DOI: 10.21037/gs.2017.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-related lymphedema: risk factors, precautionary measures, and treatments

Abstract: Breast cancer-related lymphedema (BCRL) is a negative sequela of breast cancer treatment, and well-established risk factors include axillary lymph node dissection (ALND) and regional lymph node radiation (RLNR). BCRL affects approximately 1 in 5 patients treated for breast cancer, and it has a significant negative impact on patients' quality of life after breast cancer treatment, serving as a reminder of previous illness. This paper is a comprehensive review of the current evidence regarding BCRL risk factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
210
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(225 citation statements)
references
References 189 publications
(331 reference statements)
7
210
0
8
Order By: Relevance
“…A well-studied, independent risk factor for BCRL is high BMI, defined as BMI > 30 kg/m 2 [35,50,56-60] . Jamallo et al [62] and other smaller studies have also correlated this finding that women with BMI of 30 kg/m 2 or greater, were at least 3.6 times more likely to develop BCRL [53,61] . Furthermore, Jamallo et al [62] found that post-operative weight fluctuations greater than 10 pounds per month, either lost or gained, increased BCRL [53] .…”
Section: Incidence and Risk Factorsmentioning
confidence: 67%
See 2 more Smart Citations
“…A well-studied, independent risk factor for BCRL is high BMI, defined as BMI > 30 kg/m 2 [35,50,56-60] . Jamallo et al [62] and other smaller studies have also correlated this finding that women with BMI of 30 kg/m 2 or greater, were at least 3.6 times more likely to develop BCRL [53,61] . Furthermore, Jamallo et al [62] found that post-operative weight fluctuations greater than 10 pounds per month, either lost or gained, increased BCRL [53] .…”
Section: Incidence and Risk Factorsmentioning
confidence: 67%
“…Jamallo et al [62] and other smaller studies have also correlated this finding that women with BMI of 30 kg/m 2 or greater, were at least 3.6 times more likely to develop BCRL [53,61] . Furthermore, Jamallo et al [62] found that post-operative weight fluctuations greater than 10 pounds per month, either lost or gained, increased BCRL [53] . With this information, counseling patients about healthy weight, as well managing weight fluctuations, can contribute to helping to decrease the incidence of BCRL with this well-known, modifiable risk factor.…”
Section: Incidence and Risk Factorsmentioning
confidence: 67%
See 1 more Smart Citation
“…MLD performed by a therapist was more effective than self-massage in reducing edema [16], and more effective when CDT was applied with MLD [21]. MLD is more effective when applied with other compression methods, such as garment and bandaging, pneumatic compression, and limb exercise, in order to decrease lymphedema [15,22]. MLD was studied because of its effects in decreasing lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Otros factores están relacionados con las características de la mujer como la obesidad, el tabaquismo, entre otros. Algunas de las recomendaciones para reducir el riesgo de linfedema están centradas en un manejo interdisciplinario de manera preventiva y correctiva; como es el uso de método ganglio centinela para reducir en gran medida el número de ganglios a extirpar, así como el uso de manga de compresión y rehabilitación temprana del brazo afectado [24][25][26] .…”
Section: Discussionunclassified